Method for forming multilayer coating film and multilayer coating film formed thereby

By using a top coating composition containing hydroxyl-containing acrylic resin, polyisocyanate compound and resin beads, the weather resistance and moisture resistance of the multi-layer coating film in the prior art are solved, and the low temperature is achieved Cured pearlescent multi-layer coating and improves thermal insulation.

CN119497649APending Publication Date: 2025-02-21BASF COATINGS GMBH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380052305.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-08
Filing Date
2023-06-12
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the prior art, when forming a multi-layer coating film, it is necessary to form a transparent coating film layer on the uppermost layer, otherwise it will affect the weather resistance and moisture resistance of the coating film, and the high-temperature curing requirements are high, and other effects are not satisfactory.

Method used

Using a top coating composition containing hydroxyl-containing acrylic resin, polyisocyanate compound and resin beads, the composition is applied to the colored coating layer and cured to form a pearlescent multi-layer coating film without needing Transparent coating layer.

Benefits of technology

The pearlescent multi-layer coating film cured at low temperatures has better weather resistance and moisture resistance, and ensures that the multi-layer coating film has better thermal insulation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005231041850000211
    Figure BDA0005231041850000211
  • Figure BDA0005231041850000251
    Figure BDA0005231041850000251
  • Figure HDA0005231041860000011
    Figure HDA0005231041860000011
Patent Text Reader

Abstract

Provided is a method in which a pearlescent multilayer coating film is formed using a topcoat composition that does not contain a glossy pigment, such as an interference pigment, which cures at a low temperature and has better weather resistance and moisture resistance even if a clear coating film layer is not formed on the uppermost layer. Further, a multilayer coating film formed by such a method is provided. [Solution] This problem is solved by: a method for forming a multilayer coating film in which a colored coating film layer containing a colored pigment is formed on an object to be coated, and applying thereon a glossy pigment-free top coat composition containing a hydroxyl group-containing acrylic resin (A), a polyisocyanate compound (B), and resin beads (C) to form a top coat layer, curing the top coat layer, in which the resin beads (C) have a specified average particle diameter D50, the dry film thickness of the top coat layer is equal to or less than the average particle diameter D50 of the resin beads (C), and the dry film thickness of the top coat layer is equal to or less than the average particle diameter D50 of the resin beads (C). The brightness difference (L * 15-L * 25) of the obtained multi-layer coating film is within a specified range; and a multilayer coating film formed by such a method.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for forming a pearlescent multilayer coating film using a coating composition containing no lustrous pigment such as an interference pigment, and to a multilayer coating film formed by the method. [Background Technology]

[0002] Pearlescent paint colors containing optical interference pigments that change color depending on the viewing angle have recently gained popularity due to providing a sense of premium quality, particularly in fields such as automobile exterior panels and household appliances. Such pearlescent coating films can generally be obtained by applying a pearlescent coating composition containing interference pigments that define a pearlescent texture to a colored base coating composition that defines the hue and brightness of a multilayer coating film, and applying a clear coating thereon to protect the coating film.

[0003] For example, Patent Document 1 discloses a method for forming a multilayer coating film by forming an electrodeposition coating film, a colored intermediate coating film, a glossy coating film containing an interference pigment, and a clear coating film on an automobile body, wherein the use of a specific colored intermediate coating film allows the formation of a pearlescent heat-insulating multilayer coating film.

[0004] Meanwhile, for design purposes, attempts have been made to add resin beads to coating compositions. For example, patent document 2 discloses a powder coating material that forms a wavy texture, which comprises a thermosetting powder coating component and resin beads. This powder coating can form a coating film with a soft, unique, satin-like wavy texture in the form of a uniform, complex, fine, circular raised pattern. Patent document 3 discloses a paint matting method in which resin beads with a specific refractive index are added to a film-forming component that can form a transparent layer. This method enables the formation of a top coating film that appears transparent and has less gloss.

[0005] [Prior art literature]

[0006] [Patent Document]

[0007] [Patent Document 1] Japanese Unexamined Patent Application No. 2016-36759

[0008] [Patent Document 2] Japanese Unexamined Patent Application No. 9-302272

[0009] [Patent Document 3] Japanese Unexamined Patent Application No. 5-65429 [Summary of the invention]

[0010] [Problems to be Solved by the Invention]

[0011] However, in the method for forming a multilayer coating film in Patent Document 1, a clear coating film layer must be formed on the uppermost layer. Failure to form a clear coating layer on the uppermost layer will affect the weather resistance and moisture resistance of the resulting coating film, making it difficult to use it outdoors. The invention in Patent Document 2 is a thermosetting powder coating, thus resulting in the need for a high heating temperature of 150°C to 280°C. Patent Document 3 discloses only a matte effect obtained by adding resin beads, but other effects are not satisfactory.

[0012] An object of the present invention is to provide a method in which a pearlescent multilayer coating film is formed using a top coating composition containing no glossy pigment such as an interference pigment, the pearlescent multilayer coating film being cured at a low temperature and having better weather resistance and moisture resistance even without forming a clear coating layer on the uppermost layer.

[0013] Another object of the present invention is to provide a multi-layer coating film formed by the above method for forming a multi-layer coating film.

[0014] [Methods of solving the problem]

[0015] As a result of extensive studies to solve the above-mentioned problems, the inventors perfected the present invention when they found that these problems were solved by: a method for forming a multi-layer coating film, wherein a colored coating film layer containing a color pigment is formed on an object to be coated, and a top coating composition containing no glossy pigment and containing a hydroxyl-containing acrylic resin (A), a polyisocyanate compound (B) and resin beads (C) is applied thereon to form a top coating layer, which is cured, wherein the resin beads (C) have a specified average particle size D50, the dry film thickness of the top coating layer is equal to or less than the average particle size D50 of the resin beads (C), and the brightness difference value (L*15-L*25) of the obtained multi-layer coating film is within a specified range.

[0016] Specifically, in the present invention, these problems are solved by a method for forming a multilayer coating film, the method comprising:

[0017] Step (1): a step in which a colored coating composition containing a color pigment is applied to an object to be coated to form a colored coating layer;

[0018] Step (2): a step in which a top coating composition containing no glossy pigment and containing a hydroxyl-containing acrylic resin (A), a polyisocyanate compound (B) and resin beads (C) is applied onto the colored coating film layer to form a top coating layer; and

[0019] Step (3): a step of curing the colored coating layer formed in step (1) and the top coating layer formed in step (2) by heating them separately or simultaneously, wherein

[0020] The average particle size D50 of the resin beads (C) is 20 to 70 μm,

[0021] The dry film thickness of the top coating is equal to or less than the average particle size D50 of the resin beads (C), and

[0022] The difference between the L*15 value and the L*25 value (L*15-L*25) is 1.0 to 20.0, wherein the L*15 value indicates the brightness based on the spectral reflectance of reflected light according to the CIELAB color system, wherein the incident light falling at an angle of 45 degrees relative to the vertical line of the obtained multi-layer coating surface is measured at an angle of 15 degrees relative to the specular reflection angle (incident light direction); and the L*25 value indicates the brightness based on the spectral reflectance of reflected light according to the CIE LAB color system, wherein the incident light falling at an angle of 45 degrees relative to the vertical line of the obtained multi-layer coating surface is measured at an angle of 25 degrees relative to the specular reflection angle (incident light direction).

[0023] In the method for forming a multilayer coating film of the present invention, the total content of the resin beads (C) in the top coating composition is preferably 5 to 40 parts by mass per 100 parts by mass of the total nonvolatile components of the hydroxyl-containing acrylic resin (A) and the polyisocyanate compound (B).

[0024] The method of the present invention is preferably a method for forming a multi-layer coating film in which the top coating composition contains a color pigment.

[0025] The method of the present invention is preferably a method for forming a multi-layer coating film, wherein the top coating layer is cured by heating it to between 70°C and 150°C.

[0026] The method of the present invention is preferably a method for forming a multilayer coating film in which the L*45 value of the color coating film layer is 70 to 95, and the infrared reflectivity (IRSR) of the obtained multilayer coating film is 60% or more.

[0027] In the present invention, these problems are also solved by a multilayer coating film obtained by the above method for forming a multilayer coating film.

[0028] [Effects of the invention]

[0029] In the method for forming a multilayer coating film of the present invention, a top coating composition not containing a glossy pigment such as an interference pigment can be used to form a pearlescent multilayer coating film, which can be cured at a low temperature and has better weather resistance and moisture resistance even without forming a clear coating film layer on the uppermost layer. It is also possible to ensure that such a multilayer coating film has a better heat insulation effect. [Drawings]

[0030] [ Figure 1 ] Figure 1Schematic diagram illustrating a method for measuring the brightness difference of the multi-layer coating film of the present invention. Figure 1 (a) shows the specular reflection of light incident on the coating, and Figure 1 (b) shows the reflected light used to measure brightness. [Specific implementation method]

[0031] [Step (1)]

[0032] In step (1) of the method for forming a multilayer coating film of the present invention, a colored coating composition containing a color pigment is first applied to an object to be coated to form a colored coating film layer.

[0033] [Object to be coated]

[0034] Examples of objects that can be coated using the method for forming a multilayer film coating of the present invention include, but are not particularly limited to, components made of metals such as iron, zinc, aluminum, and magnesium, components made of alloys of these metals, components on which these metals are applied by electroplating or vapor deposition, and components made of, for example, glass, plastic, or a variety of foamed materials, among which steel materials and plastic materials used for constructing automobile bodies are preferred. These components can be treated, for example, by means of a degreasing treatment or a surface treatment as required.

[0035] When the above-mentioned member is used as the object to be coated in the present invention, a primer coating film can also be formed thereon. The primary coating film is applied to the surface of the member so as to, for example, cover the surface of the member or make the member corrosion-resistant, rust-resistant or sticky, and can be formed by applying a primer coating and then curing or drying. Examples of primer coating materials that can be used include but are not particularly limited to well-known materials, such as electrodeposition coatings, solvent-based primers, and water-based primers.

[0036] [Colored coating composition]

[0037] The colored coating composition used in the method for forming a multi-layer coating film of the present invention contains a resin component and a color pigment.

[0038] The resin component of the colored coating composition used in the present invention may be a thermosetting resin composition which is applied and then heated to form a coating film as a crosslinking reaction proceeds, or may be a thermoplastic resin composition which forms a coating film as a solvent is volatilized away.

[0039] Examples of thermosetting resin compositions include those comprising: a base resin, such as an acrylic resin, a polyester resin, an alkyd resin, and an urethane resin, having a crosslinkable functional group such as a hydroxyl group; and a crosslinking agent, such as a melamine resin, a urea resin, or a polyisocyanate compound (including those blocked). These can be used when dissolved or dispersed in a solvent (such as an organic solvent and / or water). The content of the crosslinking agent in the resin composition (base resin+crosslinking agent) is not particularly limited, but is preferably 10 to 100 parts by mass, more preferably 20 to 80 parts by mass, and particularly preferably 30 to 60 parts by mass / 100 parts by mass of the total amount of non-volatile components of the resin.

[0040] Examples of thermoplastic resin compositions include compositions containing base resins having a mass average molecular weight of 30,000 or more, such as acrylic resins, polyester resins, alkyd resins, urethane resins, polyolefin resins (including chlorinated and / or modified ones) and epoxy resins. These can be used while being dissolved or dispersed in a solvent such as an organic solvent and / or water.

[0041] Examples of color pigments in the colored coating composition used in the present invention include: inorganic pigments, such as titanium oxide pigments, iron oxide pigments, titanium yellow, or other composite oxide pigments; organic pigments, such as azo pigments, quinacridone pigments, diketopyrrolopyrrole pigments, perylene pigments, pyrenone pigments, benzimidazolone pigments, isoindoline pigments, isoindoline ketone pigments, metal chelate azo pigments, phthalocyanine pigments, anthraquinone pigments, dioxazine pigments, reduced pigments and indigo pigments; and carbon black. It is preferred to use, for example, azo black pigments, perylene black pigments and metal oxide black pigments instead of carbon black pigments, because the resulting multilayer coating film will have a better heat insulation effect. These color pigments can be used alone or in combination of two or more.

[0042] The total content of the color pigments in the colored coating composition used in the present invention is not particularly limited, but is preferably 10 to 200 parts by mass, more preferably 30 to 180 parts by mass, and particularly preferably 50 to 160 parts by mass per 100 parts by mass of the total amount of the non-volatile components of the resin used as a carrier.

[0043] The colored coating composition used in the present invention may also contain a gloss pigment. Examples of gloss pigments include colorless or colored aluminum pigments, vapor-deposited metal flake pigments, optical interference pigments obtained by coating a transparent or translucent substrate with a metal oxide, and the like. These gloss pigments may be used alone or in combination of two or more.

[0044] The total content of the gloss pigment in the colored coating composition used in the present invention is not particularly limited, but is preferably 0 to 2.0 parts by mass, more preferably 0 to 1.0 parts by mass, and particularly preferably 0 to 0.5 parts by mass per 100 parts by mass of the total amount of the non-volatile components of the resin used as a carrier.

[0045] In addition, the following items can be blended in the colored coating composition used in the present invention as needed: solvent, such as organic solvent and / or water; various additives used in coatings, such as rheology control agents, pigment dispersants, anti-settling agents, curing catalysts, defoamers, antioxidants and UV absorbers; and body pigments. Examples of organic solvents include those conventionally used to produce colored coating compositions, such as: aromatic hydrocarbons, such as toluene, xylene and aromatic naphtha; ketones, such as acetone, methyl ethyl ketone and methyl amyl ketone; esters, such as ethyl acetate, butyl acetate, 2-butoxyethyl acetate, amyl acetate and ethyl ethoxypropionate; alcohols, such as isopropanol, butanol and 2-butoxyethanol; ethers; aliphatic hydrocarbons, including chlorinated hydrocarbons; or mixtures thereof. In the case where polyisocyanate compounds (including those blocked) are used as crosslinking agents, organic solvent alcohols or water should be avoided to ensure a relatively stable curing reaction.

[0046] The content of the nonvolatile component used when applying the colored coating composition of the present invention is not particularly limited, but is preferably 10.0 to 65.0% by mass, more preferably 15.0 to 63.0% by mass, and particularly preferably 20.0 to 60.0% by mass.

[0047] The colored coating composition used in the present invention can be applied by methods such as electrostatic coating, air spraying or airless spraying; the thickness of the colored coating film after curing is not particularly limited, but is preferably 5 to 50 μm, more preferably 10 to 45 μm, and particularly preferably 15 to 40 μm.

[0048] The L*45 value indicating brightness according to the CIE LAB color system (spectral reflectance based on reflected light, where incident light falling at an angle of 45 degrees relative to a vertical line on the surface of the resulting multilayer coating film is measured at an angle of 45 degrees relative to the specular reflection angle (direction of incident light)) is not particularly limited, but a value of 70 to 95 will ensure that the resulting multilayer coating film has a better heat-insulating effect. The L*45 value is more preferably 75 to 93, and particularly preferably 80 to 90. The CIE LAB color system is a color system specified by the International Commission on Illumination (CIE) in 1976; it is also adopted in JISZ 8781-4:2013. The brightness L*45 value in the present invention is a value measured using a multi-angle spectrophotometer BYK-mac i (trade name, manufactured by BYK Gardner Co., Ltd.).

[0049] [Step (2)]

[0050] In step (2) of the method for forming a multilayer coating film of the present invention, a top coating composition is applied onto the color coating layer to form a top coating layer.

[0051] [Top coating composition]

[0052] The top coating composition used in the method for forming a multi-layer coating film of the present invention comprises a hydroxyl-containing acrylic resin (A), a polyisocyanate compound (B) and resin beads (C), but does not contain a glossy pigment.

[0053] [Hydroxy-containing acrylic resin (A)]

[0054] The hydroxyl-containing acrylic resin (A) used in the present invention can be obtained by a known method (such as free radical copolymerization of a monomer mixture containing a hydroxyl-containing acrylic monomer). Examples of hydroxyl-containing acrylic monomers include: esters, such as 2-hydroxyethyl acrylic acid or methacrylate, 2-hydroxypropyl ester, 3-hydroxypropyl ester or 4-hydroxybutyl ester; and ε-caprolactone or ethylene oxide or propylene oxide ring-opening adducts of 2-hydroxyethyl acrylic acid or methacrylate. These hydroxyl-containing acrylic monomers can be used alone or in combination of two or more.

[0055] Examples of other monomers that can be copolymerized with the above hydroxyl-containing acrylic monomers include: acrylic acid or methacrylic acid, and methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, hexyl, cyclohexyl, 2-ethylhexyl, lauryl and stearyl esters thereof; and acrylonitrile, methacrylonitrile, acrylamide, methacrylamide, styrene, α-methylstyrene, maleic acid and vinyl acetate. These copolymerizable monomers can be used alone or in combination of two or more with the above hydroxyl-containing acrylic monomers.

[0056] The hydroxyl value of the hydroxyl-containing acrylic resin (A) is determined based on the content of the hydroxyl-containing acrylic monomer in the monomers to be copolymerized. The hydroxyl value of the hydroxyl-containing acrylic resin (A) used in the present invention is not particularly limited, but is preferably 80 to 200 mgKOH / g, more preferably 90 to 190 mgKOH / g, and particularly preferably 100 to 180 mgKOH / g.

[0057] The glass transition temperature of the hydroxyl-containing acrylic resin (A) is determined based on the ratio in which the monomers to be copolymerized have been blended. The glass transition temperature of the hydroxyl-containing acrylic resin (A) used in the present invention is not particularly limited, but is preferably -50°C to 70°C, more preferably -45°C to 65°C, and particularly preferably -40°C to 60°C. The glass transition temperature in the present invention is a value calculated by the formula shown below.

[0058] 1 / Tg=Σ(Wi / Tgi)

[0059] Tg: Copolymer glass transition temperature (absolute temperature)

[0060] Wi: mass percentage of monomer i

[0061] Tgi: glass transition temperature of the homopolymer of monomer i (absolute temperature)

[0062] The mass average molecular weight of the hydroxyl-containing acrylic resin (A) is determined based on the reaction conditions during copolymerization. The mass average molecular weight of the hydroxyl-containing acrylic resin (A) used in the present invention is not particularly limited, but is preferably 2,000 to 20,000, more preferably 3,000 to 18,000, and particularly preferably 4,000 to 16,000. The mass average molecular weight can be determined, for example, as a value calculated based on the weight average molecular weight of polystyrene using tetrahydrofuran (THF) as an eluent at a temperature of 40 ° C and a flow rate of 1 mL / min by gel permeation chromatography (GPC) obtained data. Here, the gel permeation chromatography (GPC) column can be, for example, a combination of TSKgel G2000HXL, G3000HXL, G4000HXL, and G5000HXL (trade name, manufactured by Tosoh Corporation, Japan).

[0063] [Polyisocyanate compound (B)]

[0064] The polyisocyanate compound (B) used in the present invention is not particularly limited, provided that it is a polyisocyanate compound for coating applications, wherein a variety of polyisocyanate compounds can be used, such as aromatic, aliphatic and alicyclic polyisocyanate compounds.Preferred examples of such polyisocyanate compounds include toluene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), xylene diisocyanate (XDI), hexamethylene diisocyanate (HDI), lysine diisocyanate (LDI), 2-isocyanatoethyl-2,6-diisocyanatohexanoate (LTI), isophorone diisocyanate (IPDI), trimethylhexamethylene diisocyanate (TMDI) and hydrogenated xylene diisocyanate (H6XDI).For example, these biuret, adduct and isocyanurate can also be used.For example, some of these isocyanate groups can be modified with amino-containing silane coupling agents.These polyisocyanate compounds can be used alone or in combination of two or more.

[0065] In the top coating composition used in the present invention, the ratio of the isocyanate group in the polyisocyanate compound (B) is preferably 0.4 to 1.6 mol, more preferably 0.6 to 1.4 mol, and particularly preferably 0.8 to 1.2 mol per 1 mol of the hydroxyl group in the hydroxyl-containing acrylic resin (A).

[0066] [Resin beads (C)]

[0067] The average particle size D50 of the resin beads (C) used in the present invention is preferably 20 to 70 μm, more preferably 30 to 65 μm, and particularly preferably 40 to 60 μm. An average particle size D50 of 20 μm or more will improve the pearlescent appearance, while an average particle size D50 of 70 μm or less can prevent the spray gun from being clogged during coating.

[0068] As used in the present invention, the average particle size D50 is the particle size of 50% of the total volume of particles from the minimum particle size to a given particle size in the cumulative particle size distribution measured by laser diffraction / scattering (static light scattering), expressed as a volume percentage of all particles. Examples of devices for measuring particle size distribution by laser diffraction / scattering (static light scattering) include Partica LA-960V2 series (trade name, manufactured by Horiba, Ltd.), SALD-2300 (trade name, manufactured by Shimadzu Corporation) and MT3000II series (trade name, manufactured by Microtrac Bel Corp.).

[0069] The resin beads (C) preferably have a spherical shape with a smooth surface, but may have a quasi-spherical shape with a wavy texture on the surface. However, columnar or needle-like shapes are not recommended because it may be difficult to achieve the expected pearlescent appearance. The resin beads (C) may have a cross-linked or non-cross-linked structure, provided that the shape is stable during the thermal curing process. The resin beads (C) may also contain, for example, a colorant (such as an organic pigment and an inorganic pigment) and a stabilizer (such as an antioxidant and a UV absorber).

[0070] For example, the resin composition or synthesis route of the resin beads (C) is not particularly limited; resin beads such as polyamide (nylon) resins, polyolefin resins, acrylic resins, polystyrene resins, epoxy resins, polyester resins, urethane resins and melamine resins can be used. Typical examples of commercially available resin beads include: VESTOSCINT 1164 and VESTOSCINT 2157 (trade names, manufactured by Daicel-Evonik Ltd.); ORGASOL 1002D NAT1, ORGASOL 1002ES5 NAT1, ORGASOL 2002D NAT1, ORGASOL 2002ES3 NAT3, ORGASOL 2002ES4NAT3, ORGASOL 2002ES5 NAT3, ORGASOL 2002ES6 NAT3, and ORGASOL 3502DNAT1 (trade names, manufactured by Arkema); MIPELON XM-220 and MIPELON XM-330 (trade names, manufactured by Mitsui Chemicals, Inc.), CHEMISNOW MX-2000, CHEMISNOW MX-3000, CHEMISNOW MZ-20HN, CHEMISNOW MZ-30H, CHEMISNOW SGP-70C, and CHEMISNOW SGP-150C (product names, manufactured by Soken Chemical & Engineering); TECHPOLYMER MBX-20, TECHPOLYMER MBX-30, TECHPOLYMER MBX-40, TECHPOLYMER MBX-50, TECHPOLYMER MBX-60, TECHPOLYMER MB30X-20, TECHPOLYMER MB20X-30, TECHPOLYMER MBX-25H, TECHPOLYMER SSX-120, TECHPOLYMER SSX-127, TECHPOLYMER MBP-20, TECHPOLYMER SBX-30, TECHPOLYMER BM30X-30, TECHPOLYMER BM30X-55, TECHPOLYMER ABX-20, TECHPOLYMER ARX-30, TECHPOLYMER AFX-30, and TECHPOLYMER MB-20 (trade names, manufactured by Sekisui Kasei Co., Ltd.);and TAFTIC AR650M, TAFTIC AR650MX, TAFTIC AR650MZ, and TAFTICFH-S020 (trade names, manufactured by Japan Exlan Co., Ltd.); and RUBCOLEUR 030(X)Clear (trade name, manufactured by Dainichiseika Color & Chemicals Co., Ltd.). The resin beads may be used alone or in combination of two or more. .

[0071] In the top coating composition used in the present invention, the total content of the resin beads (C) is preferably 5 to 40 parts by mass, more preferably 15 to 35 parts by mass, and particularly preferably 10 to 30 parts by mass per 100 parts by mass of the total non-volatile components of the hydroxyl-containing acrylic resin (A) and the polyisocyanate compound (B). A content of the resin beads (C) of 5 parts by mass or more ensures that a unique design effect can be achieved, and a content of the resin beads (C) of up to 40 parts by mass ensures weather resistance and moisture resistance.

[0072] The top coating composition used in the present invention may also include color pigments. Examples of color pigments include: inorganic pigments, such as titanium oxide pigments, iron oxide pigments, titanium yellow, or other composite oxide pigments; organic pigments, such as azo pigments, quinacridone pigments, diketopyrrolopyrrole pigments, perylene pigments, pyrenone pigments, benzimidazolone pigments, isoindoline pigments, isoindoline ketone pigments, metal chelate azo pigments, phthalocyanine pigments, anthraquinone pigments, dioxazine pigments, reducing pigments and indigo pigments; and carbon black. It is preferred to use, for example, azo-based black pigments, perylene-based black pigments and metal oxide black pigments instead of carbon black pigments, because the resulting multilayer coating film will have a better heat insulation effect. These color pigments can be used alone or in combination of two or more.

[0073] The total color pigment content in the top coating composition used in the present invention is not particularly limited, but is preferably 0 to 50 parts by mass, more preferably 2 to 40 parts by mass, and particularly preferably 5 to 35 parts by mass per 100 parts by mass of the total non-volatile components of the hydroxyl-containing acrylic resin (A) and the polyisocyanate compound (B). However, the top coating composition of the present invention does not contain a glossy pigment because weather resistance and moisture resistance may be impaired.

[0074] In addition, the following items may be blended in the top coating composition used in the present invention as needed: solvents, such as organic solvents; various additives used in coatings, such as rheology control agents, pigment dispersants, anti-settling agents, curing catalysts, defoamers, antioxidants and UV absorbers; and body pigments. Examples of organic solvents include those conventionally used to produce top coating compositions, such as: aromatic hydrocarbons, such as toluene, xylene and aromatic naphtha; ketones, such as acetone, methyl ethyl ketone and methyl amyl ketone; esters, such as ethyl acetate, butyl acetate, 2-butoxyethyl acetate, amyl acetate and ethyl ethoxypropionate; ethers; aliphatic hydrocarbons, including chlorinated hydrocarbons; or mixtures thereof. However, alcohols are not recommended because they may hinder the curing reaction.

[0075] The content of the nonvolatile component used when applying the top coating composition of the present invention is not particularly limited, but is preferably 56.0 to 72.0% by mass, more preferably 58.0 to 70.0% by mass, and particularly preferably 60.0 to 68.0% by mass.

[0076] The top coating composition used in the present invention can be applied by methods such as electrostatic coating, air spraying, and airless spraying.

[0077] The thickness of the cured top coating used in the present invention is preferably equal to or less than the average particle size D50 of the resin beads. Ensuring that the thickness (average thickness) of the cured top coating is equal to or less than the average particle size D50 of the resin beads will improve the pearlescent appearance. In particular, the thickness of the cured top coating is preferably 60% to 95%, and particularly preferably 65% ​​to 80%, relative to the average particle size D50 of the resin beads. In the present invention, the cured thickness is the average value of any 10 approximately equidistant points on a 10 cm x 20 cm sample measured using an electromagnetic film thickness meter DELTASCOPE FMP10 (trade name, manufactured by Helmut Fischer Group).

[0078] [Step (3)]

[0079] In step (3) of the method for forming a multilayer coating film of the present invention, the colored coating film layer formed in step (1) and the top coating layer formed in step (2) are heated separately or simultaneously to obtain a cured multilayer coating film.

[0080] In the present invention, when the colored coating and the top coating are heated separately, the first heating is performed between step (1) and step (2), and the second heating is performed after step (2). When heated separately, the conditions of the first heating and the second heating may be the same or different.

[0081] In the present invention, if the color coating and the top coating are heated simultaneously, heating is performed only after step (2). When heating simultaneously, for example, preheating or blowing may be performed between step (1) and step (2), provided that the coating film is not substantially cured.

[0082] Among these options of the present invention, in order to facilitate the appearance of, for example, a multilayer coating film, the following is preferred: a colored coating film layer is formed and then allowed to stand or preheat at room temperature, a top coating film is then formed thereon, and then the colored coating film layer and the top coating film are heated simultaneously.

[0083] In the present invention, heating can be accomplished by known means; for example, a drying furnace such as an air heating furnace, an electric furnace, or an infrared induction heating furnace can be used. The heating temperature is not particularly limited, but is preferably 70°C to 150°C, more preferably 70°C to 125°C, and particularly preferably 70°C to 100°C. A heating temperature of 70°C or higher can ensure that the curing reaction proceeds well, while a temperature as high as 150°C will help control energy consumption. The heating time is also not particularly limited, but is preferably 10 to 50 minutes, more preferably 15 to 40 minutes, and particularly preferably 20 to 30 minutes.

[0084] The multi-layer coating film obtained by the method for forming a multi-layer coating film in the present invention has a pearlescent appearance that changes color depending on the viewing angle.

[0085] In order to obtain an excellent pearlescent appearance, the brightness difference L*15-L*25 of the multilayer coating film of the present invention is set within a specific range as described below. As described above, brightness L* is defined in JIS Z8781-4:2013, and its use in the present invention is referred to below. Figure 1 Further explanation.

[0086] Figure 1 (a) is a cross-sectional view of the multilayer coating film 10, which shows light falling at an angle of 45 degrees relative to the vertical line PL of the coating film surface F of the multilayer coating film 10. When the incident light I is incident at an angle R of 45° relative to the vertical line PL of the coating film surface F, I When the light falls to the ground and is specularly reflected on the coating surface F, the reflection angle of the specularly reflected light SR is, specifically, the specular reflection angle R sr Perpendicular to (90°) incident angle R I .

[0087] In the present invention, the dry film thickness of the top coating layer is equal to or less than the average particle size D50 of the resin beads (C), resulting in the formation of a specific wavy texture on the upper surface of the multilayer coating film 10. In order to give the multilayer coating film 10 a pearl-like appearance, the reflection of the surface F of the resulting coating film is maintained within a certain range by selecting, for example, the dry film thickness of the multilayer coating film 10, the shape and average particle size D50 of the resin beads (C), and the total content of the resin beads (C) in the top coating composition, thereby ensuring that the multilayer coating film has excellent pearl luster.

[0088] like Figure 1 (b) shows that relative to the mirror reflection angle R SR The incident light I (at the reflection angle R) is reflected at an angle of 15 degrees (direction of incident light) L15 The reflected light L 15 (indicated by a dotted line)) is measured as L*15 (indicating brightness according to the CIE LAB color system based on spectral reflectance) by a measuring device (not shown).

[0089] Relative to the mirror reflection angle R SR The incident light I (at the reflection angle R) is reflected at an angle of 25 degrees (direction of incident light) L25 The reflected light L 25 (indicated by a dotted line)) is measured as L*25 (indicating brightness according to the CIELAB color system based on spectral reflectance) by a measuring device (not shown). The surface state of the multilayer coating film of the present invention, i.e., the pearly appearance, is specified by the difference between the two brightness values ​​at two reflection angles measured in this way, L*15-L*25.

[0090] The brightness L*15 value and L*25 value in the present invention are values ​​measured using a multi-angle spectrophotometer BYK-mac i (trade name, manufactured by BYK Gardner). In the multi-layer coating film of the present invention, the brightness difference L*15-L*25 is preferably 1.0 to 20.0, more preferably 1.5 to 15.0, and particularly preferably 2.0 to 10.0. A brightness difference L*15-L*25 of 1.0 to 20.0 will ensure that the multi-layer coating film has an excellent pearlescent appearance.

[0091] The multilayer coating film obtained in the present invention also preferably has an infrared reflectivity (IRSR) of 60% or more, more preferably 63% or more, and particularly preferably 65% ​​or more. An infrared reflectivity (IRSR) of 60% or more will ensure that the resulting multilayer coating film has a better heat insulation effect. Here, the infrared reflectivity (IRSR) in the present invention is a value measured using an ultraviolet / visible / near infrared spectrophotometer UV-3600 (trade name, manufactured by Shimadzu Corporation).

[0092] The multilayer coating film obtained in the present invention has a total solar reflectance (TSR) of preferably 60% or more, more preferably 63% or more, and particularly preferably 65% ​​or more. A total solar reflectance (TSR) of 60% or more will ensure that the resulting multilayer coating film has a better heat insulation effect. As used in the present invention, the total solar reflectance (TSR) is a value measured using an ultraviolet / visible / near infrared spectrophotometer UV-3600 (trade name, manufactured by Shimadzu Corporation).

[0093] The method for forming a multilayer coating film in the present invention and the multilayer coating film obtained thereby are suitable for bodies, components and parts of automobiles such as passenger cars, trucks, motorcycles and buses, and are particularly effective for automobile bodies when the coated object is metal, and are particularly effective for interior and exterior parts of automobile bodies when the coated object is plastic.

[0094] [Example]

[0095] The present invention is described in more detail by, but not limited to, the following examples. In the examples, unless otherwise specified, "parts" means "parts by mass", and "%" of the blended amount and content means "% by mass".

[0096] <Production Example 1: Production of polyurethane resin dispersion PU-1 for water-based colored coating composition>

[0097] (1) Production of polyester polyol solution PP-1

[0098] A flask equipped with a reflux condenser (with a separation tube for reaction water), a thermometer, a stirrer and a nitrogen feed tube was charged with 35.0 parts of dimer acid PRIPOL 1017 (trade name, manufactured by Croda Japan; based on C36 dicarboxylic acid produced by dimerization of C18 unsaturated fatty acids), 30.0 parts of isophthalic acid, 0.6 parts of adipic acid, 33.6 parts of 1,6-hexanediol and 0.8 parts of trimethylolpropane; the raw material contents were dissolved by heating them to 120°C, and then heated to 160°C while stirring. The contents were maintained at 160°C for 1 hour, and then heated to 230°C over a period of 5 hours. The acid value was periodically measured while the contents were maintained at 230°C; when the resin acid value reached 4 mgKOH / g, the contents were cooled to at least 80°C. Finally, 60.8 parts of methyl ethyl ketone were added to obtain a polyester polyol solution PP-1. The polyester polyol solution PP-1 was characterized by a mass average molecular weight of 7,200, an acid value of 4 mgKOH / g, a hydroxyl value of 62 mgKOH / g, and a resin solids content of 60%.

[0099] (2) Production of polyurethane resin dispersion PU-1

[0100] Into a flask equipped with a thermometer, a stirrer and a nitrogen feed tube were charged 110.0 parts of the polyester polyol solution PP-1 obtained in Production Example 1-(1), 4.5 parts of dimethylolpropionic acid, 2.0 parts of neopentyl glycol and 20.3 parts of methyl ethyl ketone, and the contents were heated to 80° C. while stirring. When the temperature had reached 80° C., 24.0 parts of isophorone diisocyanate were added, maintaining the temperature at 80° C.; when the isocyanate content reached 0.40 mmol / g, 3.2 parts of trimethylolpropane were added, maintaining the temperature at 80° C.; when the isocyanate content reached 0.03 mmol / g, 5.2 parts of butyl cellosolve were added; after the contents had been cooled to 50° C., 3.3 parts of dimethylethanolamine were added to neutralize the acid groups, and 150.0 parts of deionized water were added. The contents were then heated to 100°C and methyl ethyl ketone was removed under reduced pressure to obtain polyurethane resin dispersion PU-1. Polyurethane resin dispersion PU-1 was characterized by a mass average molecular weight of 71,000, an acid value of 21 mgKOH / g, a hydroxyl value of 21 mgKOH / g, and a resin solid content of 38%.

[0101] <Production Example 2: Production of Polyester Resin Solution PE-1 for Water-Based Colored Coating Composition>

[0102] Into a flask equipped with a reflux condenser (with a separation tube for reaction water), a thermometer, a stirrer and a nitrogen feed tube, 15.0 parts of the above dimer acid PRIPOL 1017 (trade name, manufactured by Croda Japan Co., Ltd.), 30.0 parts of isophthalic anhydride, 3.1 parts of adipic acid, 31.5 parts of 1,6-hexanediol and 10.3 parts of trimethylolpropane were charged; the raw material content was dissolved by heating it to 120°C, and then heated to 160°C while stirring. The content was maintained at 160°C for 1 hour, and then heated to 230°C over a period of 5 hours. The content was maintained at 230°C for 2 hours and then heated to 180°C. Then 10 parts of trimellitic anhydride were added, and the acid value was periodically measured while the content was maintained at 180°C; when the acid value reached 25 mgKOH / g, the content was cooled to at least 80°C. 25 parts of butyl cellosolve were added, 3.2 parts of dimethylethanolamine were added to neutralize the acid groups, and 34.1 parts of deionized water were added to obtain a polyester resin solution PE-1. The polyester resin solution PE-1 was characterized by a mass average molecular weight of 15,000, an acid value of 25 mgKOH / g, a hydroxyl value of 90 mgKOH / g, and a resin solid content of 60%.

[0103] <Production Example 3: Production of Water-Based Colored Coating Composition PR-1>

[0104] (1) Production of water-based colored coating composition PR-1

[0105] To 26.3 parts of polyurethane resin dispersion PU-1 (dispersion resin) and 33.3 parts of polyester resin solution PE-1, 119.0 parts of titanium dioxide pigment Ti-Pure R706 (trade name, manufactured by Chemours), 1.0 parts of perylene-based black pigment Paliogen Black L0086 (trade name, manufactured by DIC Corporation) and 30.0 parts of deionized water (to adjust viscosity) were added; the contents were dispersed using a Motormill to obtain a pigment paste. Then 52.6 parts of polyurethane resin dispersion PU-1 were weighed out, 209.6 parts of the above pigment paste were added, and the contents were mixed while stirring in a dissolver. 27.8 parts of melamine resin solution CYMEL 203 (trade name, manufactured by Allnex; non-volatile component content: 72% by mass), 12.5 parts of melamine resin solution CYMEL 325 (trade name, manufactured by Allnex; non-volatile component content: 80% by mass), 33.3 parts of polyester resin solution PE-1 and 40.0 parts of deionized water were added thereto and mixed. Finally, the mixture was diluted with deionized water to a Ford #4 cup viscosity of 40 seconds at 20° C. to obtain a water-based colored coating composition PR-1.

[0106] (2) Evaluation of water-based colored coating layers

[0107] CathoGuard 500 (trade name, manufactured by BASF Japan) was applied to a zinc phosphate treated mild steel plate via electrodeposition to a cured film thickness of 20 μm, and baked at 175°C for 25 minutes to obtain an electrodeposition coated sheet. The water-based color coating composition PR-1 was then sprayed on the electrodeposition coated sheet to a dry film thickness of 30 μm, and preheated to 85°C for 5 minutes. It was then heated to 100°C for 30 minutes to obtain a water-based colored coating layer. The brightness L*45 value of the resulting water-based colored coating layer was 87 as measured using a multi-angle spectrophotometer BYK-mac i (trade name, manufactured by BYK Gardner).

[0108] <Production Example 4: Production of Solvent-Based Colored Coating Composition PR-2>

[0109] (1) Production of solvent-based pigmented coating composition PR-2

[0110] To 200.0 parts of a maleic anhydride-modified chlorinated polypropylene resin solution SUPERCHLON 842LM (trade name, manufactured by Nippon Paper Industries; non-volatile component content: 20% by mass; mass average molecular weight: 55,000) as a resin dispersion, 50.0 parts of toluene, 139.0 parts of a titanium dioxide pigment Ti-Pure R706 (trade name, manufactured by Chemours) and 1.0 part of a perylene-based black pigment Paliogen Black L0086 (trade name, manufactured by DIC Corporation) were added; the contents were dispersed using a Motormill to obtain a pigment paste. Then 200.0 parts of the maleic anhydride-modified chlorinated polypropylene resin solution SUPERCHLON 842LM was weighed out, 390.0 parts of the above pigment paste was added, and the contents were mixed while stirring in a dissolver. 13.3 parts of blocked isocyanate resin solution Desmodur BL 3175SN (trade name, manufactured by Sumika Covestro Urethane Co., Ltd.; non-volatile component content: 75% by mass; NCO content: 11.1% by mass), 10.0 parts of liquid epoxy resin jER828 (trade name, manufactured by Mitsubishi Chemical Corporation) and 100.0 parts of aromatic petroleum naphtha Solvesso 100 (trade name, ExxonMobil) were added thereto and mixed. Finally, the resulting mixture was diluted with a solvent mixture consisting of toluene / aromatic petroleum naphtha Solvesso 100 (trade name, ExxonMobil) (1:1 mass ratio) to a Ford #4 cup viscosity of 15 seconds at 20° C. to obtain a solvent-based colored coating composition PR-2.

[0111] (2) Evaluation of solvent-based pigmented coatings

[0112] CathoGuard 500 (trade name, manufactured by BASF Japan) was applied to a zinc phosphate treated mild steel plate via electrodeposition to a cured film thickness of 20 μm, and baked at 175°C for 25 minutes to obtain an electrodeposition coated sheet. Then a solvent-based colored coating composition PR-2 was sprayed on the electrodeposition coated sheet to a dry film thickness of 20 μm, and preheated to room temperature for 5 minutes. It was then heated to 100°C for 30 minutes to obtain a solvent-based colored coating layer. The brightness L*45 value of the resulting solvent-based colored coating layer was 85 as measured using a multi-angle spectrophotometer BYK-mac i (trade name, manufactured by BYK Gardner).

[0113] <Production Example 5: Production of Hydroxyl-Containing Acrylic Resin Solution A-1 for Top Coating Composition>

[0114] A four-necked flask equipped with a thermometer, a reflux condenser, a stirrer and a dropping funnel was charged with 33.9 parts of xylene, which was heated and maintained at 140° C. while being stirred in a nitrogen stream. Then at a temperature of 140° C., the following substances were uniformly mixed therein by dropwise addition at a constant rate over a period of 2 hours via a dropping funnel: a free radical polymerizable monomer (23.9 parts of 4-hydroxybutyl acrylate, 10.0 parts of styrene, 19.0 parts of isobutyl methacrylate, 6.2 parts of cyclohexyl methacrylate and 0.9 parts of methacrylic acid) and 5.0 parts of tert-butyl peroxy-2-ethylhexanoate (as a polymerization initiator). After the dropwise addition of these materials was completed, the contents were maintained at a temperature of 140° C. for 1 hour, and then the reaction temperature was lowered to 110° C. Then 0.1 parts of tert-butyl peroxy-2-ethylhexanoate (polymerization initiator) was dissolved in 1.0 parts of xylene and added as an additional catalyst, the temperature of 110° C. was maintained for another 2 hours, and then the contents were cooled to obtain a hydroxyl-containing acrylic resin solution A-1. The hydroxyl-containing acrylic resin solution A-1 was characterized by a mass average molecular weight of 7,000, an acid value of 9.8 mgKOH / g, a hydroxyl value of 155 mgKOH / g, a glass transition temperature of −10° C., and a resin solid content of 60%.

[0115] <Production Example 6: Production of Hydroxyl-Containing Acrylic Resin Solution A-2>

[0116] A four-necked flask equipped with a thermometer, a reflux condenser, a stirrer and a dropping funnel was charged with 27.0 parts of xylene and 9.0 parts of propylene glycol monomethoxy ether acetate, which was heated and maintained at 130° C. while being stirred in a nitrogen stream. Then, at a temperature of 130° C., the following substances were uniformly mixed therein by dropwise addition at a constant rate over a period of 3 hours via a dropping funnel: a free radical polymerizable monomer (12.1 parts of 4-hydroxybutyl acrylate, 3.9 parts of 2-hydroxyethyl acrylate, 25.0 parts of styrene, 4.1 parts of isobutyl methacrylate, 9.1 parts of cyclohexyl methacrylate and 0.8 parts of methacrylic acid) and 1.0 parts of tert-butyl peroxy-2-ethylhexanoate (as a polymerization initiator). After the dropwise addition of these materials was completed, the contents were maintained at a temperature of 130° C. for 1 hour, and then the reaction temperature was lowered to 110° C. Then 0.1 parts of tert-butyl peroxy-2-ethylhexanoate (polymerization initiator) was dissolved in 1.0 parts of xylene and added as an additional catalyst, the temperature of 110°C was maintained for another 2 hours, and then 6.9 parts of xylene were added to dilute the solution, which was cooled to obtain a hydroxyl-containing acrylic resin solution A-2. The hydroxyl-containing acrylic resin solution A-2 is characterized by a mass average molecular weight of 10,000, an acid value of 9.5 mgKOH / g, a hydroxyl value of 120 mgKOH / g, a glass transition temperature of 25°C, and a resin solid content of 55%.

[0117] <Production Example 7: Production of White Pigment Paste W-1>

[0118] 50.0 parts of hydroxyl-containing acrylic resin solution A-1 (as a dispersing resin), 120.0 parts of titanium dioxide pigment TIPAQUE CR-95 (trade name, manufactured by Ishihara Sangyo Co., Ltd.), and 50.0 parts of xylene were mixed and then dispersed using a Motormill to obtain white pigment paste W-1.

[0119] <Production Example 8: Production of White Pigment Paste W-2>

[0120] 54.5 parts of hydroxyl-containing acrylic resin solution A-2 (as a dispersing resin), 120.0 parts of titanium dioxide pigment TIPAQUE CR-95 (trade name, manufactured by Ishihara Sangyo Co., Ltd.) and 45.5 parts of xylene were mixed and then dispersed using a Motormill to obtain white pigment paste W-2.

[0121] <Production Example 9: Production of Yellow Pigment Paste Y-1>

[0122] 100.0 parts of hydroxyl-containing acrylic resin solution A-1 (as a dispersing resin), 40.0 parts of yellow iron oxide pigment TAROX LL-100 (trade name, manufactured by Titan Kogyo Ltd.), and 100.0 parts of xylene were mixed and then dispersed using a Motormill to obtain yellow pigment paste Y-1.

[0123] <Production Example 10: Production of Yellow Pigment Paste Y-2>

[0124] 109.1 parts of hydroxyl-containing acrylic resin solution A-2 (as a dispersing resin), 40.0 parts of yellow iron oxide pigment TAROX LL-100 (trade name, manufactured by Titanium Industries Co., Ltd.), and 90.9 parts of xylene were mixed and then dispersed using a Motormill to obtain yellow pigment paste Y-2.

[0125] <Production Example 11: Production of Black Pigment Paste B-1>

[0126] 100.0 parts of hydroxyl-containing acrylic resin solution A-1 (as a dispersing resin), 20.0 parts of perylene-based black pigment Paliogen Black L0086 (trade name, manufactured by DIC Corporation) and 100.0 parts of xylene were mixed and then dispersed using a Motormill to obtain black pigment paste B-1.

[0127] <Production Example 12: Production of Top Coating Compositions TC-1 to TC-14>

[0128] The hydroxyl-containing acrylic resin (A), resin beads (C), pigment paste and additive solution (UV absorber solution, light stabilizer solution and surface conditioner solution) listed in Table 1 were mixed and stirred until uniform. The polyisocyanate compound (B) listed in Table 1 was added to the mixture, and the mixture was stirred again until uniform. The resulting mixture was diluted with Solvesso 100 (denoted as S-100 in Table 1) to a Ford #4 cup viscosity of 25 seconds at 20° C. to obtain top coating compositions TC-1 to TC-14.

[0129] Solvesso 100 (trade name, manufactured by ExxonMobil Corporation) is an aromatic naphtha; the amount (parts by mass) of Solvesso 100 used to adjust each top coating composition to the above-mentioned viscosity is shown in the S-100 row of Table 1.

[0130]

[0131] The numerical values ​​in the table indicate parts by mass.

[0132] 1) Desmodur N3300: trade name, manufactured by Sumika Covestro Urethane Co., Ltd.; hexamethylene diisocyanate (HDI) trimer; non-volatile component content: 100% by mass; NCO content: 21.8% by mass

[0133] 2) TECHPOLYMER MBX-20: trade name, manufactured by Sekisui Chemical Co., Ltd.; acrylic resin beads; D50 = 20 μm

[0134] 3) TAFTIC AR650MX: trade name, manufactured by Japan Ixlan Co., Ltd.; acrylic resin beads; D50 = 40 μm

[0135] 4) TAFTIC AR650MZ: trade name, manufactured by Japan Ixlan Co., Ltd.; acrylic resin beads; D50 = 60 μm

[0136] 5) ORGASOL 2002ES6 NAT3: trade name, manufactured by Arkema; ​​polyamide resin beads; D50 = 60 μm

[0137] 6) TECHPOLYMER MBX-12: trade name, manufactured by Sekisui Chemical Co., Ltd.; acrylic resin beads; D50 = 12 μm

[0138] 7) TAFTIC AR650ML: trade name, manufactured by Japan Ixlan Co., Ltd.; acrylic resin beads; D50 = 80 μm

[0139] 8) Iriodin 103WNT: Trade name, manufactured by Merck Performance Materials Ltd.: Interference pearl pigment

[0140] 9) UV absorber solution: 20% by mass xylene solution of TINUVIN 900 (trade name, manufactured by BASF Japan)

[0141] 10) Light stabilizer solution: 20% by mass xylene solution of TINUVIN 292 (trade name, manufactured by BASF Japan)

[0142] 11) Surface conditioner solution: 10% by mass xylene solution of BYK-300 (trade name, manufactured by BYK Japan)

[0143] <Examples 1 to 10, and Comparative Examples 1 to 7>

[0144] (1) Sample preparation

[0145] CathoGuard 500 (trade name, manufactured by BASF Japan) cationic electrodeposition paint was applied to a zinc phosphate treated mild steel plate via electrodeposition to a cured film thickness of 20 μm and baked at 175° C. for 25 minutes to obtain an electrodeposition coated sheet.

[0146] In Examples 1 to 8 and Comparative Examples 1 to 7, the water-based color coating composition PR-1 was then sprayed on the above electrodeposition-coated sheets to a dry film thickness of 30 μm and preheated to 85° C. for 5 minutes. The sheets coated with the water-based color coating composition PR-1 were then cooled to room temperature, and then the top coating compositions TC-1 to TC-12 were sprayed to the dry film thicknesses given in Table 2, and the specimens were allowed to stand at room temperature for 10 minutes. Finally, the sheets were heated to 100° C. for 30 minutes to obtain specimens.

[0147] In Examples 9 and 10, the solvent-based color coating composition PR-2 was spray dried to a dry film thickness of 20 μm on the above-mentioned electrodeposition-coated sheets and allowed to stand at room temperature for 5 minutes, and then the top coating compositions TC-13 and TC-14 were sprayed to the dry film thickness given in Table 2, and the specimens were allowed to stand at room temperature for 10 minutes. Finally, the sheets were heated to 100° C. for 30 minutes to prepare multilayer coating film specimens.

[0148] Details of the resin beads contained in each top coating composition are given in Table 1, and Table 2 also shows the average particle size D50 of the resin beads in each top coating composition.

[0149] Topcoat composition TC-11 clogged the spray gun during the coating process and no specimens could be prepared.

[0150] (2) Evaluation of multi-layer coatings

[0151] The multilayer coating films (specimens) obtained in Examples 1 to 10 and Comparative Examples 1, 2, and 4 to 7 were evaluated and analyzed according to (2)-1 to (2)-5 below, and the results are presented in Table 2.

[0152] (2)-1 Evaluation of the brightness difference L*15-L*25

[0153] The lightness L*15 value and L*25 were measured using a multi-angle spectrophotometer BYK-mac i (trade name, manufactured by BYK Gardner Co.) to calculate a lightness difference value L*15-L*25.

[0154] (2)-2 Measurement of infrared reflectivity (IRSR)

[0155] The infrared reflectance (IRSR) was measured using an ultraviolet / visible / near-infrared spectrophotometer UV-3600 (trade name, manufactured by Shimadzu Corporation).

[0156] (2)-3 Measurement of Total Solar Reflectance (TSR)

[0157] The total solar reflectance (TSR) was measured using an ultraviolet / visible / near-infrared spectrophotometer UV-3600 (trade name, manufactured by Shimadzu Corporation).

[0158] (2)-4 Evaluation of moisture resistance

[0159] The obtained specimen was allowed to stand for 240 hours in a constant temperature and humidity chamber set at 50° C. and 95% humidity. The specimen was then taken out and visually evaluated for abnormality or blistering in the coating film appearance based on the following criteria.

[0160] O: No abnormality in the coating

[0161] X: Blistering or significant abnormality in appearance

[0162] (2)-5 Weather resistance evaluation

[0163] The test was performed for 3000 hours using a sunlight carbon arc lamp type weathering tester (JIS K-5400 (1990) 9.8.1), and the coating film was visually evaluated after the test.

[0164] O: No abnormality in the coating

[0165] X: Blistering or significant abnormality in appearance

[0166]

[0167] The invention accomplished by the inventors has been described in detail based on the embodiments, but the present invention is not limited to these embodiments, and it is obvious that the present invention can be modified in various ways within the scope of the present invention.

[0168] [Explanation of symbols]

[0169] 10: Multi-layer coating

[0170] F: Surface of multi-layer coating

[0171] PL: vertical lines on the surface of multi-layer coatings

[0172] I: Incident light

[0173] R I : Angle of incidence

[0174] SR: Specular Reflection

[0175] R SR : Specular reflection angle

[0176] L 15 : Reflected light (relative to the mirror reflection angle R SR Light reflected at an angle of 15 degrees (direction of incident light)

[0177] L 25 : Reflected light (relative to the mirror reflection angle R SR Light reflected at an angle of 25 degrees (direction of incident light)

Claims

1. A method for forming a multilayer coating film, the method comprising: Step (1): a step in which a colored coating composition containing a color pigment is applied to an object to be coated to form a colored coating layer; Step (2): a step in which a top coating composition containing no glossy pigment and comprising a hydroxyl-containing acrylic resin (A), a polyisocyanate compound (B) and resin beads (C) is applied onto the colored coating film layer to form a top coating layer; as well as Step (3): a step of curing the colored coating layer formed in step (1) and the top coating layer formed in step (2) by heating them separately or simultaneously, wherein: The average particle size D50 of the resin beads (C) is 20 to 70 μm, The dry film thickness of the top coating is equal to or less than the average particle size D50 of the resin beads (C), and The difference between the L*15 value and the L*25 value (L*15-L*25) is 1.0 to 20.0, wherein the L*15 value indicates the brightness based on the spectral reflectance of reflected light according to the CIELAB color system, wherein the incident light falling at an angle of 45 degrees relative to the vertical line of the obtained multi-layer coating surface is measured at an angle of 15 degrees relative to the specular reflection angle (incident light direction); and the L*25 value indicates the brightness based on the spectral reflectance of reflected light according to the CIE LAB color system, wherein the incident light falling at an angle of 45 degrees relative to the vertical line of the obtained multi-layer coating surface is measured at an angle of 25 degrees relative to the specular reflection angle (incident light direction).

2. The method for forming a multilayer coating film according to claim 1, wherein The total content of the resin beads (C) in the top coating composition is 5 to 40 parts by mass per 100 parts by mass of the total non-volatile components of the hydroxyl-containing acrylic resin (A) and the polyisocyanate compound (B).

3. The method for forming a multilayer coating film according to claim 1 or 2, wherein: The topcoat composition contains color pigments.

4. The method for forming a multilayer coating film according to claim 1 or 2, wherein: The topcoat layer is cured by heating it to between 70°C and 150°C.

5. The method for forming a multilayer coating film according to claim 1, wherein The L*45 value of the colored coating layer is 70 to 95, and the infrared reflectivity (IRSR) of the resulting multilayer coating is 60% or more. 6 . A multi-layer coating film formed by the method for forming a multi-layer coating film according to claim 1 .

Citation Information

Patent Citations

  • Delustering method for paint, paint and coated product

    JP1993065429A

  • Forming method for pearl-tone heat-shielding double layered coating film and heat-shielding double layered coating film obtained from the same

    JP2016036759A